1995
DOI: 10.1111/j.1468-2885.1995.tb00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Dialectic of Control and Emancipation in Organizing for Social Change: A Multitheoretic Study of the Grameen Bank in Bangladesh

Abstract: In recent years, the Grameen (rural) Bank of Bangladesh gained international fame for successfully organizing grassroots microenterprises for productive self-employment and social change. The Grameen Bank provides collateral-free loans and various social services for the poor, charging 20% interest on capital' and yet maintaining a 99% loan recovery rate. Many of the bank's I. 9 million members, of whom 94% are women, attribute their present well-being to its ameliorative qualities. Using multiple theories (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 31 publications
(32 reference statements)
1
41
0
Order By: Relevance
“…This study, therefore concurs with scholars like Burrell (1992) and Reedy and Learmouth (2009), who encourage management/business scholars to study alternative organizations -the other 2% in the study by House and Aditya (1997). Fruitful cases for bringing the SL/DL discourse forward can be found among employee-owned cooperatives (Rothschild-Whitt, 1986;Summers, 2004); knowledge-intensive organizations dominated by experts (Alvesson, 2004;Klenke, 1997); new organizational forms such as the Grameen Bank (Papa et al, 1995); or in the performing arts as demonstrated by Koivunen (2007). Further qualitative micro level studies in shared leadership settings are required to explore the mechanisms of rotational leadership, possibly using Day et al's (2004) IMOI model.…”
Section: Suggested Future Researchsupporting
confidence: 86%
“…This study, therefore concurs with scholars like Burrell (1992) and Reedy and Learmouth (2009), who encourage management/business scholars to study alternative organizations -the other 2% in the study by House and Aditya (1997). Fruitful cases for bringing the SL/DL discourse forward can be found among employee-owned cooperatives (Rothschild-Whitt, 1986;Summers, 2004); knowledge-intensive organizations dominated by experts (Alvesson, 2004;Klenke, 1997); new organizational forms such as the Grameen Bank (Papa et al, 1995); or in the performing arts as demonstrated by Koivunen (2007). Further qualitative micro level studies in shared leadership settings are required to explore the mechanisms of rotational leadership, possibly using Day et al's (2004) IMOI model.…”
Section: Suggested Future Researchsupporting
confidence: 86%
“…Finally, the findings contribute to Papa, Auwal, and Singhal's (1995) original conceptualization of the dialectic of emancipation and control by placing it in a new context. This dialectic is virtually unexplored.…”
Section: Discussionmentioning
confidence: 88%
“…This study develops the dialectic by viewing it in a specific type of relationship. By characterizing the dialectic through the accounts of the interviewees, this study adds another dimension to Papa, Auwal, and Singhal's (1995) conceptualization, by contributing to a better understanding of the "helping" relationship typical of most shelters for battered women.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations